The Influence Of Community Spirit In Gaining Education On Andrea Hirata's The Rainbow Troops Novel : A Sociological Approach - FITRIANA, MEILA (2012)
The problem of this study is how community spirit influence in gaining education is reflected in Andrea Hirata's The Rainbow Troops novel. The objective of this study is to analyze the novel based on the structural elements and to analyze the novel based on the sociological approach. This study belongs to qualitative method. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is the novel itself, meanwhile the secondary data sources are other materials related to the study. Both data are collected through library research and analyzed by descriptive analysis. Based on the analysis the researcher draws the following conclusions. First, based on the structural analysis of each element, it shows that the character and characterization, setting, plot, point of view, style, and theme are related to each other and form the unity into good quality of novel. Second, based on the sociological analysis, there is a close relationship between the novel story and the reality of Indonesian life. Andrea Hirata describes the society life under the poverty condition.